1997
DOI: 10.1007/s002770050277
|View full text |Cite
|
Sign up to set email alerts
|

Blood concentrations of G-CSF and myelopoiesis in patients undergoing aortocoronary bypass surgery

Abstract: The pattern of changes in leukocyte counts and the blood concentration of G-CSF were observed in 15 patients undergoing aortocoronary bypass surgery. Myelopoietic function was assessed by examining the myelogram and performing flow cytometry to identify human leukocyte differentiation antigens on bone marrow aspirates obtained from the sternum when opening and closing the sternotomy. The blood concentration of G-CSF increased gradually after removal of the aortic cross clamp and peaked on the first postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The neutrophil phenotype commonly seen during active bone marrow neutrophil release is unique and suggestive of neutrophil membrane immaturity. CABG, a controlled inflammatory stimulus associated with bone marrow neutrophil release (Quiroga et al, 1985;Usui et al, 1997), provides a useful in vivo model to investigate changes in the circulating neutrophil pool during acute inflammation. We have identified that over 40% of the circulating neutrophil pool following CABG exhibits a CD10 ) /CD16 low phenotype, that this subpopulation is functionally significant and may provide a useful quantitative measure of the bone marrow contribution to neutrophilia.…”
Section: Discussionmentioning
confidence: 99%
“…The neutrophil phenotype commonly seen during active bone marrow neutrophil release is unique and suggestive of neutrophil membrane immaturity. CABG, a controlled inflammatory stimulus associated with bone marrow neutrophil release (Quiroga et al, 1985;Usui et al, 1997), provides a useful in vivo model to investigate changes in the circulating neutrophil pool during acute inflammation. We have identified that over 40% of the circulating neutrophil pool following CABG exhibits a CD10 ) /CD16 low phenotype, that this subpopulation is functionally significant and may provide a useful quantitative measure of the bone marrow contribution to neutrophilia.…”
Section: Discussionmentioning
confidence: 99%